2008
DOI: 10.1007/s12275-007-0214-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of polychlorinated biphenyl-dechlorinating populations in contaminated sediments

Abstract: Polychlorinated biphenyl (PCB)-dechlorinating microorganisms were characterized in PCB-contaminated sediments using amplified ribosomal DNA restriction analysis (ARDRA). The sediments were prepared by spiking Aroclor 1248 into PCB-free sediments, and were inoculated with microorganisms eluted from St. Lawrence River sediments. PCB-free sediments inoculated with the same inoculum served as the control. Four restriction fragment length polymorphism (RFLP) groups in the eubacterial and two in the archaeal domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…The enriched culture dechlorinated five of the most toxic, dioxin-like coplanar PCB congeners with rate and extent remarkably higher than those reported so far in the literature [31]. Similarly to other reports [8,18], the archaeal population was mainly composed by members of the Methanomicrobiales and Methanosarcinales subgroups, that apparently were not involved in the dechlorination process. One Chloroflexi bacterium having similarity with bacterium SF1, a clone identified as the PCB dechlorinator in estuarine, sediment-free cultures [12] was detected in the developed cultures.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The enriched culture dechlorinated five of the most toxic, dioxin-like coplanar PCB congeners with rate and extent remarkably higher than those reported so far in the literature [31]. Similarly to other reports [8,18], the archaeal population was mainly composed by members of the Methanomicrobiales and Methanosarcinales subgroups, that apparently were not involved in the dechlorination process. One Chloroflexi bacterium having similarity with bacterium SF1, a clone identified as the PCB dechlorinator in estuarine, sediment-free cultures [12] was detected in the developed cultures.…”
Section: Discussionsupporting
confidence: 58%
“…The occurrence of Methanosaeta spp. has been detected in previous studies on microbial communities of PCB-dechlorinating slurry cultures of estuarine [8] and river sediments [18]. However, in both cases their enrichment was observed in PCB-free controls rather than in the actively PCB-dechlorinating cultures, thus suggesting that they are not directly involved in PCB dechlorination.…”
Section: Characterization Of Archaeal Communitiesmentioning
confidence: 66%
See 1 more Smart Citation
“…Thus, a Draft addressed to regulate the use of sludge as fertilizer on the basis of its contamination has been developed by the European Commission [10]. In particular, concentration limits were suggested for the following pollutants: halogenated organic compounds (AOX), linear alkylbenzene sulfonates (LAS), di(2-ethylhexyl)phthalate (DEHP), nonylphenol and nonylphenolethoxylates with 1 or 2 ethoxy groups (NPE), some polycyclic aromatic hydrocarbons (specifically: acenaphthene, phenanthrene, fluorene, fluoranthene, pyrene, benzo(b+j+k)fluoranthene, benzo(a)pyrene, benzo(ghi)perylene and indeno(1,2,3-c,d)pyrene), PCB congener numbers 28,52,101,118,138,153, 180 and polychlorinated dibenzodioxins/dibenzofurans (PCDD/F) [10]. Thus, sludge resulting from wastewater treatment processes containing the above mentioned pollutants at concentrations higher than those indicated by the EC Draft should be subjected to a dedicated treatment before being used as a fertilizer in agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…The DLG includes several cultivated strains of the genus Dehalococcoides and many sequences of uncultivated organisms that have been found mostly in marine sediment or subsurface locations. Another obligate OHR bacterial species, Dehalobacter sp., from the phylum Firmicutes, was found in a culture enriched with dibenzo-p-dioxins (Yoshida et al, 2009) and in sediments spiked with Aroclor 1248 (Oh et al, 2008). Hiraishi (2008) showed that different members of the Chloroflexi phylum exhibited a limited range of PCB congener dechlorination capacity, which strongly suggested a complex mechanism and the possible significance of synergistic interactions with the contribution of other phyla to the transformation of these compounds.…”
Section: Introductionmentioning
confidence: 97%